---------------------------------------------------
Question
---------------------------------------------------
x - 2 = √(x + 10)
---------------------------------------------------
Square both sides
---------------------------------------------------
(x - 2)² = (√(x + 10))²
(x - 2)² = (x + 10) ← square and square root would will net off each other
---------------------------------------------------
Remove brackets
---------------------------------------------------
x² - 4x + 2² = x + 10
x² - 4x + 4 = x + 10
---------------------------------------------------
minus x + 10 on both sides
---------------------------------------------------
x² - 4x + 4 - x - 10 = 0
x² - 5x - 6 = 0
---------------------------------------------------
Factorise the left side
---------------------------------------------------
(x - 6)(x + 1) = 0
---------------------------------------------------
Apply zero product property
---------------------------------------------------
x -6 = 0 or x +1 = 0
---------------------------------------------------
Solve x
---------------------------------------------------
x = 6 or x = -1
---------------------------------------------------
Answer: x = 6 or x = -1
---------------------------------------------------